DYNAMICS OF ATTENTION DISTRIBUTION DURING UNILATERAL RADIOTHERAPY - Danilov, G.V.; Krotkova, O.A.; Alekseeva, A.N.; Kuleva, A.Yu.; Kaverina, M. Yu.; Galkin, M.V.; Enikolopova, E.V. (Modern Psychology, 2019)
The immediate consequences of radiotherapy for extracerebral tumors adjacent to hippocampus from the basal surface of the brain were studied. Normal brain structures including hippocampus are affected by therapeutic irradiation with this kind of treatment. The participants of the investigation were 23 patients with meningiomas of chiasm-sellar region (12 – with left-sided tumors and 11 – with right-sided). The patients were tested two times: before radiotherapy and immediately after the last fraction of irradiation. The control group included 40 healthy volunteers, who also were tested two times. The data obtained indicates the effect of redistribution of visual attention after irradiation of the right hemisphere. We hypothesize the greater sensitivity of the right hemisphere to irradiation.